Parasitic fauna infections in Pashmina goats of cold arid region of Ladakh, India - MAQBOOL, I; WANI, Z A; ALLAIE, I M; SHAHARDAR, R A; BABA, F A; ASHRAF, AIMAN (The Indian Journal of Animal Sciences, 2016)
This preliminary study based on examination of 60 faecal samples was carried out on traditionally raised Pashmina goats (Capra siberica) of Ladakh region during the year, 2014. Out of 60 samples, 34 (56.66%) were positive for one or the other parasite species. Strongyle worm eggs including Nematodirus (26.66%), Moniezia (15.00%), Trichuris (1.66%) and oocysts of Eimeria (28.33%) were recovered. Pure natural infection with Nematodirus spp. was observed in 23.33% of samples. Mixed infection was observed in 15.00% of animals. The present study may be regarded as a step forward for evaluating the prevalence of parasites parasitizing the Pashmina goats of Ladakh, so as to evolve package of practices for their effective control.